Impact of prompt gamma coincidence correction on absorbed dose estimation in differentiated thyroid cancer using 124I PET/CT imaging. Issue 12 (December 2018) - Wierts, Roel; Conti, Maurizio; Claessen, Anouk G.G.; Herrmann, Ken; Kemerink, Gerrit J.; Binse, Ina; Wildberger, Joachim E.; Mottaghy, Felix M.; Backes, Walter H.; Jentzen, Walter
Abstract : Introduction: Iodine-124 positron emission tomography/computed tomography ( 124 I PET/CT) is increasingly being used in the absorbed dose estimation in the radioiodine treatment of differentiated thyroid cancer (DTC). However, the produced prompt gamma coincidences (PGCs) associated with the 124 I decay result in a bias in the absorbed dose estimation. The impact of a sinogram-based PGC correction approach on the absorbed dose estimation in 124 I PET/CT DTC imaging is investigated. Methods: 124 I phantom and patient measurements were performed on a Siemens Biograph mCT PET/CT system. All images were reconstructed with (PGCon ) and without PGC correction (PGCoff ). The phantom contained seven spheres (diameters: 6.6–37 mm). The spheres and background compartment were filled with a 124 I solution, resulting in a low (9.4 : 1) and a high sphere-to-background activity concentration ratio (750 : 1). Sphere recovery coefficient (RC) values were determined. In addition, the impact of PGC correction on measured lesion uptake and calculated lesion-absorbed dose was assessed for 66 lesions identified in 24 DTC patients. Results: PGC correction systematically increased sphere RC values up to 71% for the smallest spheres. For the patient data, PGC correction significantly increased both the measured 124 I uptake ( P <0.005) and the calculated lesion-absorbed dose ( P =0.008) by ∼3%. The percentage difference in the calculated lesion-absorbed dose ranged from −19% to 50%, showing that PGC correction had a variable and large impact for a few lesions. Conclusion: PGC correction resulted in significantly higher sphere RC values, 124 I lesion uptake values and estimated lesion-absorbed doses.